A nursing process model for a hospital - systematic literature review - Guimarães, Ana; Cruz, Isabel CF da (Online Brazilian Journal of Nursing, 2007)
To implement a model of nursing process in hospital for high complexity clients a systematic literature review will be done ti identify best practices that can be utilized.